2016
DOI: 10.1016/j.resp.2016.04.008
|View full text |Cite|
|
Sign up to set email alerts
|

The course of lung inflation alters the central pattern of tracheobronchial cough in cat—The evidence for volume feedback during cough

Abstract: The effect of volume-related feedback and output airflow resistance on the cough motor pattern was studied in 17 pentobarbital anesthetized spontaneously-breathing cats. Lung inflation during tracheobronchial cough was ventilator controlled and triggered by the diaphragm electromyographic (EMG) signal. Altered lung inflations during cough resulted in modified cough motor drive and temporal features of coughing. When tidal volume was delivered (via the ventilator) there was a significant increase in the inspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The role of pulmonary stretch receptors and, in particular, of volume-related feedback in the regulation of the cough reflex is controversial (Nishino et al, 1989b;Javorka et al, 1994;Romaniuk et al, 1997;Bolser and Davenport 2000). In a recent study, Poliacek et al (2016) found that modified lung inflations during coughing and/or additional expiratory airflow resistances altered the spatio-temporal characteristics of the cough motor pattern through volume-related feedback mechanisms similar to those operating during eupneic breathing. In the same report, an interesting discussion on lung volume feedback during coughing and the related contribution of both SARs and RARs has also been provided.…”
Section: Central Cough Pathwaysmentioning
confidence: 99%
“…The role of pulmonary stretch receptors and, in particular, of volume-related feedback in the regulation of the cough reflex is controversial (Nishino et al, 1989b;Javorka et al, 1994;Romaniuk et al, 1997;Bolser and Davenport 2000). In a recent study, Poliacek et al (2016) found that modified lung inflations during coughing and/or additional expiratory airflow resistances altered the spatio-temporal characteristics of the cough motor pattern through volume-related feedback mechanisms similar to those operating during eupneic breathing. In the same report, an interesting discussion on lung volume feedback during coughing and the related contribution of both SARs and RARs has also been provided.…”
Section: Central Cough Pathwaysmentioning
confidence: 99%
“…Another potential mechanism of CTI prolongation represents the activity of P cells which are 2nd order neurons from slowly-adapting pulmonary stretch receptors. We have shown that this afferent pathway may modulate cough, in particular reduced afferent drive from pulmonary stretch receptors prolonged CTI (Poliacek et al, 2016). It is likely that the rNTS microinjections inhibited the activity of P cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the temporal analysis (Poliacek et al, 2016, 2017a), the duration of cough-related DIA (TDIA) and ABD (TABD) activations, augmenting part of DIA (CTI =inspiratory cough phase), the time from the maximum of DIA activity to the end of cough-related ABD activity (CTE1 = active expiratory cough phase), the time from the maximum of DIA activity to the end of the cough cycle (CTE =cough expiratory phase) were measured. Further, the time between maxima of DIA and ABD activity (peaks), the quiescent period of the cough cycle (cough TE2 phase =CTE2), the duration of all cough-related EMG activity (CTactive), and the whole cough cycle duration were analysed in each stimulation period (CTtot).…”
Section: Methodsmentioning
confidence: 99%
“…pulmonary stretch receptor activation) can increase the excitability for cough [8]. However, there is no relationship of volume-timing during cough [24], there are limited correlations between I and E efforts/durations during cough [25], and the reduction of volume feedback increased I and E drive [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Upper airways inflammatory diseases and gastro-esophageal reflux disease can up regulate cough [33,34], while bronchopulmonary C-fiber activation [35], BP alterations [36] and perhaps irregular cough volumes stretch receptor activation [26] can decrease cough excitability and/or cough motor drive. We focused on those, which are easily applicable and inducible due to their potential employment for cough modulation in correction of excessive or insufficient coughing.…”
Section: Discussionmentioning
confidence: 99%